The Role of Graphene Oxide Nanocarriers in Treating Gliomas - Wang, Bin; Guo, Hanfei; Xu, Haiyang; Chen, Yong; Zhao, Gang; Yu, Hongquan (Frontiers in Oncology, 2022)
Gliomas are the most common primary malignant tumors of the central nervous system, and their conventional treatment involves maximal safe surgical resection combined with radiotherapy and temozolomide chemotherapy; however, this treatment does not meet the requirements of patients in terms of survival and quality of life. Graphene oxide (GO) has excellent physical and chemical properties and plays an important role in the treatment of gliomas mainly through four applications, viz. direct killing, drug delivery, immunotherapy, and phototherapy. This article reviews research on GO nanocarriers in the treatment of gliomas in recent years and also highlights new ideas for the treatment of these tumors.